Comparison of Copyright Laws in Indonesia and Japan as WTO Member - Amalia, Rafika (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The aim of this research is to determine the comparison of Copyright Laws in Indonesia and Japan because as members of the WTO they are obliged to refer to the TRIPs Agreement in harmonizing copyright law as their national regulations. This research uses normative legal methods with statutory and comparative conceptual approaches. The results of this research are that basically the copyright provisions in Indonesia and Japan are the same, including regarding the purpose, creator's rights, objects of protection, related rights, registration, transfer of copyright and actions that are considered infringement, but there are differences regarding the period of protection. The Indonesian Copyright Law does not yet clearly regulate sanctions for violations of moral rights.